Nitrogen plasma treatment in two-step temperature deposited FePt bilayer media - Dutta, Tanmay (2019)
Tailoring writability and obtaining better signal-to-noise ratio performance by tuning the magnetic and microstructural properties of FePt media is of great interest in the bid to achieve high areal densities for next generation hard disk drives (HDDs). Conventional ways to tune FePt media are primarily by either the insertion of additional layers, or by inclusion of segregants such as B, C, Ni, SiO2 etc. Here we describe an approach that involves modifying growth kinetics by N inclusion, via plasma treatment in FePt bilayers (consisting of a hard and a soft FePt layer). The soft FePt layer aids in obtaining easy writability, while nitrogen plasma treatment of the interface of the two FePt layers facilitates suitable tailoring of the microstructure. This approach contributed to lowering of grain dimension as well as reduction in domain sizes in the FePt bilayers, but with the unwanted side-effects of reduction in squareness and ordering. However, we further propose a method to alleviate these concerns by the deposition of the soft FePt layer in partial nitrogen atmosphere, that restored the squareness and ordering while retaining the smaller domains obtained by nitrogen plasma treatment. Thus, the proposed approach provides a potential direction towards meeting the mutually conflicting requirements of easy writability and better signal-to-noise ratio performance in FePt media.